Targeting PRAME for acute myeloid leukemia therapy - Yang, Jinjun; Chen, Mengran; Ye, Jing; Ma, Hongbing (Frontiers in Immunology, 2024)
Despite significant progress in targeted therapy for acute myeloid leukemia (AML), clinical outcomes are disappointing for elderly patients, patients with less fit disease characteristics, and patients with adverse disease risk characteristics. Over the past 10 years, adaptive T-cell immunotherapy has been recognized as a strategy for treating various malignant tumors. However, it has faced significant challenges in AML, primarily because myeloid blasts do not contain unique surface antigens. The preferentially expressed antigen in melanoma (PRAME), a cancer-testis antigen, is abnormally expressed in AML and does not exist in normal hematopoietic cells. Accumulating evidence has demonstrated that PRAME is a useful target for treating AML. This paper reviews the structure and function of PRAME, its effects on normal cells and AML blasts, its use in diagnosis and follow-up, and its use in antigen-specific immunotherapy for AML.